2018
DOI: 10.1093/ejo/cjy074
|View full text |Cite
|
Sign up to set email alerts
|

Additional appointments and discomfort associated with compliance-free fixed Class II corrector treatment: a systematic review

Abstract: Summary Objective A critical analysis of the literature to determine the prevalence and type of emergency/additional appointments, and discomfort levels associated with fixed Class II correctors. Methods Studies examining patient’s sources of discomfort or emergency appointments associated with compliance-free Class II correctors were included. Comprehensive searches up to July 2018 were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In other words, 36/58 patients experienced various complications during the appliance therapy, with an incidence of 62%. This percentage is similar to the one reported by Phuong et al 12 in their systematic review. The mean number of complications per patient was 1.4 when calculated over the whole sample.…”
Section: The Encountered Complicationssupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, 36/58 patients experienced various complications during the appliance therapy, with an incidence of 62%. This percentage is similar to the one reported by Phuong et al 12 in their systematic review. The mean number of complications per patient was 1.4 when calculated over the whole sample.…”
Section: The Encountered Complicationssupporting
confidence: 91%
“… 8 - 11 A recent systematic review investigated the prevalence of complications with fixed functional appliances, and stated that the incidence of complications is relatively high. 12 Studying the complications induced by orthodontic appliances has two main aspects: the clinician’s observations and the patients’ responses to assessment questionnaires. Regarding fixed functional appliances, the clinical perspective was previously reported with the Herbst appliance.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the main source of discomfort associated with FFRD appliances was identified as soreness in the cheeks. 36 With regard to our results, total OHIP score revealed a non-significant increase after one month wear of FFRD, declaring initial discomforts for eating/chewing and pain. The scores revealed that patients noted more issues with mastication than pain.…”
Section: Discussionmentioning
confidence: 42%
“…All of these FFA could successfully achieve class II correction even though patient discomfort and difficulties in daily clinic management may reduce their use. Removable functional appliances (RFA) have an extensive literature background with many advantages for the patient and few side effects; compliance remains the greatest problem with RFA that can ultimately lead to unfavorable results [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%